Portraits as surveillance instruments: from anthropometry to biometric faces - Gutierrez de Angelis, Marina (Revelar: Revista de Estudos da Fotografia e Imagem, 2019)
As a cultural creation, the face has a long history. Our relationship with the face is through its images: Mirrors, reflections, photographs, visions. The experience about the face deserves a genealogy, a careful attention because it is the product of a cultural construction that establishes the social status granted to the person. Different mediums of the image persisted in making faces visible or recognizable. The anthropometry of the 19th century established a new relationship between the face and the Self. Photography allowed us to explore, measure and classify the images of the face and of the human being. This explains the fascination with photography in Bertillon and Darwin. At the same time, the arrival of photography also opened the way to the era of the democratization of the face. But the images of faces that we will approach in this article are images produced by techniques of reconstruction and facial recognition based on biometric and genetic data. Biometrics seeks to recognize individuals through physical and behavioral traits, articulating an image technique with mathematical techniques. Even portraits have become instruments for surveillance. This responds to the conditioning of an apparatus that captures and determines behaviors and discourses. As Giorgio Agamben argues, certain apparatus have imposed themselves as spatial optical articulations, but also epistemic, political and ideological, capable of assuming a specific conception of the vision and position of the subject in front of the world. We define the face as an apparatus. If the history of the portrait pictures theory, as proposed by W. f. T. Mitchell, in relation to the history of the development of the process of individuation of the self, genetic biometrics dissolves it completely, since it is not a measure of the human but its negation.